Training results in increased practitioner confidence and identification of depression in people with low vision: a mixed methods study. (16th February 2021) - Bartlett, Rebecca; Acton, Jennifer H; Ryan, Barbara; Man, Ryan; Pickles, Timothy; Nollett, Claire
Abstract: Purpose: The prevalence of depression in people with low vision is high and often goes undiagnosed. There is the potential for those who provide low vision services to perform concurrent depression screening. However, prior training in depression identification and suitable referral pathways is required. The aims of this study were: (1) to assess the impact of a training programme on practitioners' confidence and behaviour in addressing depression in patients with low vision, and (2) to review the training programme and identify areas for further development. Methods: A convergent mixed methods approach was used. Questionnaires were completed by practitioners pre‐, immediately post‐ and 6 months post‐ training ( n  = 40) to assess practitioner confidence in approaching depression in patients with low vision. Qualitative interviews were performed with a subset of practitioners 6 months post‐training ( n  = 9). Additionally, routine data from the Low Vision Service Wales (LVSW) database was used to determine the change in the number of practitioners identifying depression in patients, and the change in the number of patients identified at risk of depression 6 months post‐training. Results: Of the 148 practitioners who completed low vision assessments pre‐ and post‐training, 28 (18.9%) documented risk of depression in their patients pre‐training, which increased substantially to 65 (43.9%) post‐training ( p  < 0.0001). Mixed methods analysis confirmed increased documentation of depressive symptoms by practitioners. Practitioner confidence increased following training, with 92.3% feeling more confident to approach emotional issues with patients and 92.2% intending to use the recommended screening tool to identify depression. Interviews provided insight into areas where confidence was still lacking. Quantitative questionnaires revealed that training content was considered appropriate by 91% of participants. Interviews confirmed these findings while expanding upon possibilities for programme improvement. Conclusions: Training for depression screening was found to be time‐efficient and acceptable for LVSW practitioners and shown to increase practitioner confidence in the identification of depression. Additionally, the programme changed behaviour, resulting in an increase in the identification of depression in patients with low vision. However, this is a complex topic and ongoing development is required to embed depression screening as an integral part of low vision services.